THE ROLE OF EMPLOYEE DEVELOPMENT AND TRAINING ON EMPLOYEE PERFORMANCE :A CASE STUDY OF PRIVATE HIGHER EDUCATION IN SEMARANG, CENTRAL JAVA, INDONESIA - Suparjo Suparjo; Endang Sri Sunarsih (Serat Acitya, 2018)
This study is purposed to identify the impact of employee development, training, and employee job satisfaction  towards employee performance in Private Higher Education in Semarang, Central Java, Indonesia.Two-step approach to structural equation modeling was used to test the proposed model. The sample used in this study is 200 respondents. It was taken by applying proportional random sampling.There are several findings from this study: (1) the first hypothesis is accepted, which means that there is a significant and positive influence between employee development towards employee job satisfaction  ; (2) the second hypothesis is accepted indicating that there is a significant and positive influence between training towards organizational commitment; (3) the third hypothesis is accepted which shows that there is a significant and positive influence between employee development towards employee performance; (4) the fourth hypothesis is accepted meaning that there is a significant and positive influence between training  towards employee performance; and (5)the fifth hypothesis is accepted, which means that there is a significant and positive influence between employee job satisfaction towards employee performance. Keywords: employee development, training, employee job satisfaction employee performance.